Fermentative Extraction of Coconut Oil to Maintain A Quality of Medium Chain Fatty Acid - Farid Salahudin; Nana Supriyatna (Balai Riset dan Standardisasi Industri Pontianak, 2014)
Coconut oil is healthy vegetable oil because it contains Medium Chain Fatty Acid (MCFA). The used of bleaching agent and excessive heating in coconut oil process will produce low quality oil (rancid). Therefore, it is necessary to processing that does not use chemicals and excessive heating such as fermentation using microbe and enzyme. The aim of this study was to find out the effect of bromelin enzyme concentration and Saccharomyces cereviceae fermentation to MCFA content in coconut oil. This research was done by adding the enzyme bromelain at 0, 50, 100, 200 and 400 ppm and S. cereviceae inoculated in coconut milk. The resulting oil is then tested the water content, acid number and fatty acid content. The result showed that fermentation with 200 ppm bromeline enzyme and S. cereviceae inoculation can produce the best quality coconut oil containing MCFA that meet the APCC standard.